Circumcision as conquest: Masculinity in Eswatini's voluntary medical male circumcision campaign materials - Sarah Rudrum (Taylor & Francis Group, 2023)
As a public health intervention related to sexual transmission and involving genital surgery, male circumcision for HIV prevention necessarily relates to understandings of sexuality and gender, a relationship which public health campaign materials have shaped in varying ways. Here, I employ discourse analysis to examine messages about gender and sexuality in Eswatini's Soka Uncobe (Circumcise and Conquer) public health campaign for voluntary medical male circumcision (VMMC). The slogan 'conquest' echoes nationalist imagery and extends throughout campaign materials, such as in a comic book presenting the circumcising man as a hero vanquishing an enemy. Elsewhere, campaign materials use the slogan to link sexual conquest to the conquest of HIV in a move that is misleading and potentially harmful. As with several circumcision campaigns in the region, messages about the HIV protection offered through the intervention and the limits to this protection are minimal and are overshadowed by a framing of circumcision as a newly necessary norm for appropriate masculine citizenship and sexuality. This consideration of the positioning of gender, sexuality, and sex in campaign materials promoting VMMC is pertinent to the global public health effort to reduce HIV transmission, particularly given the social complexities at stake in the context of sexual transmission.